The Role of Agriculture and Agri-Tech Investments in Nepal During a Pandemic - Karna, Poonam Kumari Labh (YASIN, 2025)
The COVID-19 pandemic has disrupted global economies, with significant implications for agriculture-dependent nations like Nepal. Agriculture, being the backbone of Nepal's economy, contributes approximately 27% to the GDP and employs over 60% of the population. However, the pandemic exposed vulnerabilities in the sector, including supply chain disruptions, labor shortages, and limited access to markets. This study explores the role of agriculture and agri-tech investments in mitigating the pandemic's impact on Nepal's agricultural sector. By analyzing the adoption of agri-tech solutions such as digital platforms, precision farming, and supply chain innovations, this research highlights how technology can enhance resilience and sustainability in agriculture. The findings suggest that agri-tech investments can improve productivity, reduce post-harvest losses, and ensure food security during crises. This study provides policy recommendations for fostering agri-tech adoption and strengthening Nepal's agricultural sector in the face of future pandemics.